A história da cidade de Santa Isabel através do olhar do Chico fotógrafo - Prado, William Jordão do (2016)
The research intends to debate, inside a historical perspective and a sociological approach, how Chico Fotógrafo's collection can help to rescue and understand the history of Santa Isabel as a city, when it is mainly oral and fragmented. It uses the hypothesis that the city will not be able to subsist for a long time only supported by orality. Because of that, the study ensures the importance of resorting to photographic records as a historical source, so that, combined, it can preserve and the non-dissipation of the places' memory. Therefore, it concludes that during a virtual age is necessary to search for a digital media able to organize, scan and share of Chico Fotografo's material as a historical source. Also, strengthens the conclusion showing as the past photograph is disseminated and preserved, it creates a democratic process. At the end, it permits the city historical knowledge and the recognition of people as being part of it, through a experience capable of interacting image and history.